Multi-objective optimisation for indentation rate, nugget diameter and tensile load in resistance spot welding using Taguchi-based grey relational analysis. (15th October 2021) - Yuce, Celalettin
In this study, a multi-objective optimisation method based on grey relational analysis with weighted responses is conducted to optimise the RSW parameters of electrode force, welding current, and welding time. Three objectives, such as indentation rate, nugget diameter, and tensile load, are simultaneously optimised. In order to assign the optimum level for each parameter individually, the Taguchi technique was applied. ANOVA results showed that the most influential parameters on indentation rate, nugget diameter, and tensile load are welding current, welding time, and welding current, respectively. In the grey relational analysis, the grey relational grades were obtained using weighted responses. The weight factors for the indentation rate, nugget diameter, and tensile load are 33.24%, 35.67%, and 31.1%, respectively. The optimum parameter combination was obtained as 2, 500 N, 9 kA, and 0.5 s. Under these parameter combinations, indentation rate, nugget diameter, and tensile load were 26.2%, 8.34 mm, and 20.04 kN, respectively.